Model Entrepreneurial Intentions of Students Vocational in Education for Enterprise Incubator Project - นิธิกิตติ์สุขเกษม, พรรณสิยา; วิงวอน, บุญฑวรรณ (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2018)
The research aimed 1) to study vocational student’s inspiration, entrepreneur’s characteristic and mentoring system of an incubator project 2) to study of the mentor system of an incubator project that influence the vocational student’s intention and 3) to study the pattern of vocational student’s entrepreneurial intentions in incubator project. By using the quantitative research method, questionnaire was distributed to 428 incubator centers. The date was analyzed by descriptive and inferential statistical method which were percentage, mean standard deviation and structural equation model (SEM.) The result from AMOS statistical software has shown the important of inspiration and mentor system were rated at high level, while the entrepreneur’s characteristic and intensions were rated at medium level. Moreover the consistency index of the structural eausal relationship model has conformed to the empirical date, where χ2 = 165.153, df = 1.46, χ2 / df = 1.18, GFI = .942, CFI = .987, RMR= .019, RMSEA = .023. The results of hypothesis testing showed that Inspiration has a direct influence on the entrepreneur’s characteristic, path coefficient value equal to .72. Entrepreneur’s characteristic had direct effect toward entrepreneurial intentions, path coefficient value equal to .61, follow by inspiration had direct effect toward the mentoring system mechanisms, path coefficient value equal to .59, the mentoring system had direct effect toward entrepreneur’s characteristic, path coefficient value equal to .18, and the mentoring system had direct effect toward entrepreneurial intentions, path coefficient value equal to .17. Model entrepreneurial intentions of students vocational in education for enterprise incubator project up to inspiration and entrepreneur’s characteristic, but mentoring system was slightly important.